Effect of Fatiguing Wheelchair Propulsion and Weight Relief Lifts on Subacromial Space in Wheelchair Users - Arnet, Ursina; Boninger, Michael L.; Cools, Ann; Bossuyt, Fransiska M. (Frontiers in Rehabilitation Sciences, 2022)
Objective: This study aimed to identify targets of intervention for reducing shoulder pain in wheelchair users with spinal cord injury (SCI) by 1) examining changes in subacromial space (acromiohumeral distance (AHD) and occupation ratio (OccRatio)) with fatiguing wheelchair propulsion, and different loading conditions (unloaded position vs. weight relief lifts (WRL)); 2) associating these changes with wheelchair user capacity, as well as 3) identifying subject characteristics associated with subacromial space, such as sex, lesion level, time since injury, body mass index and impaired shoulder range of motion. Methods: 50 manual wheelchair users with SCI (11 females, age = 50.5 (9.7) years, time since injury = 26.2 (11.4) years) participated in this quasi-experimental one-group pretest-posttest study. Ultrasound images were used to define AHD during an unloaded position, and during personal and instructed WRL before and after fatiguing wheelchair propulsion. Furthermore, supraspinatus and biceps thickness defined from ultrasound images were used to calculate OccRatios. Wheelchair user capacity was quantified as functional strength (maximum resultant force reached during maximum isometric forward push) and anaerobic work capacity (highest power output reached during 15-meter sprint test). Multilevel mixed-effects linear regression analyses controlling for between subject variability and covariables were performed to address the research questions. Results: AHD was significantly smaller during personal WRL (p<0.001) and instructed WRL (p=0.009, AHD both 11.5mm) compared to the unloaded position (11.9mm). A higher wheelchair user capacity (higher anaerobic work capacity) reduced the impact of WRL on AHD decrease. The fatiguing wheelchair propulsion had no effect on AHD (p = 0.570) and on OccRatio of supraspinatus (p = 0.404) and biceps (p = 0.448). Subject characteristics related to a larger subacromial space were lower lesion level, shorter time since injury, impaired external rotation, a lower body mass index and a higher anaerobic work capacity. Conclusion: This study showed a significant reduction in AHD during WRL with no effect of fatiguing wheelchair propulsion on the subacromial space in wheelchair users with SCI. A higher anaerobic work capacity was beneficial in stabilizing the shoulder during WRL. Our findings may assist clinicians in designing a shoulder injury prevention program.